P-112 What's the plan in 2021?. (20th March 2022) - Nolan, Lisa; Shanmugalingam, Thurkaa; Russel, Kirsty; Short, Oscar; Morley, Olivia; Tweddle, Andrew
Abstract : Background: Treatment escalation plans (TEP) are increasingly used to document individualised advance care planning decisions in acute settings. A form initially co-designed by a multi-disciplinary working group at a tertiary referral UK cancer centre during the COVID-19 pandemic was later adapted based on clinician feedback and its utilisation re-analysed. Method: A retrospective study was performed of TEP completion in adult non-elective admissions during April 2021. 100 notes were included in the final analysis (11 sets unavailable). Data gathered included patient demographics, capacity, diagnosis, disease information, prognosis and possible clinical interventions. Results: Of the 100 patients, 45% had a TEP form (53.3% in 2020). 61% were for consideration of critical care and of those for ward-based care, appropriateness of interventions was fully completed for 76%. Clinicians were more likely to record information regarding anti-cancer treatment (89%), treatment intent (80%) and concurrent problems (87%) than prognosis (62%). Of those with a TEP, 53% were for resus. However, palliative care consultation was more common in those with a TEP form (58%) than those without (18%) and mortality was higher 13.3% (with TEP) vs 0% (without TEP). Conclusion: TEP forms remain an important aspect of clinical documentation for all non-elective admissions to our tertiary referral cancer centre. However, there remains challenge in ensuring all patients have this completed during admission. Those patients with a TEP form are more likely to have palliative care consultation during their admission and therefore more likely to have advance care planning discussed.